2017
DOI: 10.1038/ncomms14164
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of the deep thermochemical structure beneath Eurasia

Abstract: A unique structure in the Earth's lowermost mantle, the Perm Anomaly, was recently identified beneath Eurasia. It seismologically resembles the large low-shear velocity provinces (LLSVPs) under Africa and the Pacific, but is much smaller. This challenges the current understanding of the evolution of the plate–mantle system in which plumes rise from the edges of the two LLSVPs, spatially fixed in time. New models of mantle flow over the last 230 million years reproduce the present-day structure of the lower man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 50 publications
(128 reference statements)
4
47
0
Order By: Relevance
“…We inserted slabs down to 1,400‐km depth in the initial condition (Figure S1). Flament et al () showed that inserting slabs to more than 800‐km depth in the initial condition better reproduces the present‐day structure of the lower mantle and that results are similar when slabs are initially inserted to more than 1,100‐km depth.…”
Section: Comparison Of Predicted Dynamic Topography With Geological Pmentioning
confidence: 99%
“…We inserted slabs down to 1,400‐km depth in the initial condition (Figure S1). Flament et al () showed that inserting slabs to more than 800‐km depth in the initial condition better reproduces the present‐day structure of the lower mantle and that results are similar when slabs are initially inserted to more than 1,100‐km depth.…”
Section: Comparison Of Predicted Dynamic Topography With Geological Pmentioning
confidence: 99%
“…In particular, we highlight that processes typically associated with supercontinents such as slab roll‐back leading to intracratonic rifting (e.g., Nanhua rift system in south China; Wang & Li, ) and the continental amalgamation of juvenile crust and evolved continental ribbons to continental masses occurred away from the established Rodinian supercontinent. This is not irreconcilable with some geodynamic modeling, which suggests that the sizable separate pieces of continental crust can also induce changes in mantle flow and structure (e.g., Flament et al, ). Further study could analyze the impact of such a subduction system as described here on mantle flow and the surface expression of the flow.…”
Section: Links To Rodiniamentioning
confidence: 96%
“…In this contribution, we aim to study the seismic structure in the D" layer near the edges of the Perm Anomaly, which was recently recognized as a small LLSVP relative to those under Africa and the Pacific (Lekic et al, 2012); it has been conjectured to separate from the African LLSVP due to the impingement of the subducted Balkan slab (van der Meer et al, 2018). Moreover, it also plays an important role in producing intraplate magmatisms-specifically, it has contributed either to the Emeishan large igneous provinces (Flament et al, 2017) or to the Siberian Traps (Torsvik & Domeier, 2017). A recent study has observed strong seismic anisotropy in the D" layer near the edges of the Perm Anomaly ; the seismic anisotropy is likely a result of the interactions between the subducted slabs and the LLSVPs (e.g., Tackley, 2011;Tan et al, 2002Tan et al, , 2011, although the existence of focused upwellings (Steinberger & Torsvik, 2012) cannot be fully ruled out.…”
Section: Citationmentioning
confidence: 99%
“…The fast anomaly detected in this study is primarily underneath west central Mongolia in which a number of seismic scatterers have been detected in the middle-lower mantle by analyzing out-of-plane P-to-P and S-to-P scattering signals (Schumacher & Thomas, 2016), indicating that the area near the western edge of the Perm Anomaly is likely composed of many isolated fast anomalies-perhaps originated from various sinking slabs. In particular, the subducted Mongol-Okhotsk (MO) slab (also named the Mongol-Kazakh anomaly; van der Meer et al, 2018) has thought to play an important role in controlling the location and evolution of the Perm Anomaly (Flament et al, 2017;Fritzell et al, 2016). However, according to the slab identification by van der Voo et al (1999) and van der Meer et al (2010van der Meer et al ( , 2018, the fast anomaly detected in this study is more likely attributed to the Central China (CC) slab (Figures 2 and 4)-representing the Paleotethyan lithosphere that subducted between North China, northeast Tibet, and Eurasia; it is presently located in the lower mantle from the CMB upward to a depth of ∼1,500 km, whereas the MO slab is probably located to the north of the CC slab (van der Meer et al, 2018).…”
Section: 1029/2019gc008195mentioning
confidence: 99%
See 1 more Smart Citation